Pengembangan Media Pembelajaran Bahasa Arab Interaktif ‘MAQIY’ untuk Meningkatkan Maharah Qira’ah Siswa Madrasah Tsanawiyah - Hamdan Nawawi, Muhammad; Afifah, Anis; Nurul Aini Lathifah, Siti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The decline in students’ motivation in learning Arabic at MTs Darul Ulum Pasinan is caused by the limited variety and interactivity of learning media. This study aims to develop an interactive learning medium called “MAQIY” to improve reading skills (maharah qirā’ah) and to test its validity and effectiveness. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 26 seventh-grade students (class VII A). Data were collected through observation, interviews, tests, questionnaires, and documentation, and analyzed using both quantitative and qualitative approaches with a one-group pre-test and post-test design.The results showed that the MAQIY media achieved a very good level of feasibility from media experts (86%), material experts (96%), and learning experts (76%). The students’ average score increased from 60.00 to 82.69 after using the media, with the results of the Paired Sample T-Test showing a significance value of 0.000 < 0.05, indicating a significant difference in learning outcomes. In conclusion, the MAQIY media is effective in improving students’ Arabic reading skills and implies the importance of developing interactive digital media in Arabic language learning at the madrasah level